Writing stories Animal stories - Ganeri, Anita (Chicago, Illinois Heinemann Library, 2013)
This book introduces readers to writing stories that revolve around animals and is a perfect resource for meeting Common Core State Standards in writing. Readers are shown how animals can be used in stories and readers are guided through the process of writing their own story. Top tips are given covering planning, writing dialogue, developing characters, adding narrative plot twists, using descriptive language and
A gift from book Africa
Arts
1 2 11 13
Keywords: Animals -- Fiction -- Authorship -- Handbooks, manuals, etc; Children's stories -- Authorship -- Handbooks, manuals, etc; Creative writing